2021
DOI: 10.1038/s41598-021-82124-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic photoplethysmography (PPG) of the radial artery through parallelized Monte Carlo and its correlation to body mass index (BMI)

Abstract: Cardiovascular disease is one of the leading causes of death in the United States and obesity significantly increases the risk of cardiovascular disease. The measurement of blood pressure (BP) is critical in monitoring and managing cardiovascular disease hence new wearable devices are being developed to make BP more accessible to physicians and patients. Several wearables utilize photoplethysmography from the wrist vasculature to derive BP assessment although many of these devices are still at the experimental… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 59 publications
2
31
0
Order By: Relevance
“…Simulations of pulse oximetry have shown that increased pigmentation reduces the overall intensity of optical signals, which can result in a degraded signal-to-noise ratio, and thus explain observations of increased measurement variability in dark-skinned people 14 . Other simulations have contradicted the conventional belief that the widely used calibration parameter is not affected by pigmentation, supporting empirical findings indicating that increased pigmentation decreases the normalized ratio 15 .…”
Section: Chetan Patil and Mohammed Shahriar Arefin The Basis Of Bias ...mentioning
confidence: 71%
“…Simulations of pulse oximetry have shown that increased pigmentation reduces the overall intensity of optical signals, which can result in a degraded signal-to-noise ratio, and thus explain observations of increased measurement variability in dark-skinned people 14 . Other simulations have contradicted the conventional belief that the widely used calibration parameter is not affected by pigmentation, supporting empirical findings indicating that increased pigmentation decreases the normalized ratio 15 .…”
Section: Chetan Patil and Mohammed Shahriar Arefin The Basis Of Bias ...mentioning
confidence: 71%
“…To perform the MCS in this study, we considered the artery as a cylinder and calculated its volume. To calculate the volume of the vessel wall, the thickness of the artery is considered as 0.2 mm [ 25 ]. As mentioned above, the arterial diameter changes according to the change in arterial pressure; the pressure–diameter relation was derived through curve fitting of the data in [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Monte Carlo modeling (MC) of the optical path and statistical modeling of waveform morphology (e.g., through Gaussian combinations) are tools that have been used to evaluate the effects of physiology or device parameters on raw PPG signal strength [ 22 , 23 , 24 ]. Chatterjee et al have used MC for this purpose [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…MC results from Oxygen saturation simulations at 660 nm and 880 nm across skin tone and source/detector separation were compared to experimentally collected data, the model was validated and the origin of the PPG signal was explored [ 24 , 25 , 26 ]. Boonya-ananta et al focused on individuals with dark skin tone and obesity, using MC to generate a single PPG period and then quantified the impact those features have on PPG AC/DC ratio [ 22 ].…”
Section: Introductionmentioning
confidence: 99%